Significance of 5'AMP-activated protein kinase in metabolomic regulation by skeletal muscle contraction - Licht Miyamoto (Japanese Society of Physical Fitness and Sports Medicine, 2015)
The number of patients exhibiting metabolic disorders has been pandemically increasing. Physical exercise is widely applied as an ideal therapeutic and preventive way against such metabolic diseases as diabetes due to its high potency of metabolic regulation. It evokes marked facilitation of glucose and lipid metabolism in contracting skeletal muscle. Recent investigations have suggested that 5'AMP-activated protein kinase (AMPK) should be a key molecule in contraction-caused metabolic changes. AMPK is activated in response to the rise in the AMP/ATP ratio following muscle contraction. The activated AMPK suppresses anabolic pathways, but increases catabolic ones to compensate for the ATP shortage. The various metabolic results of AMPK activation are similar to those in contracting skeletal muscle. However, some recent reports using genetically AMPK-disrupted animals reported that AMPK does not necessarily mediate metabolic control by muscle contraction, suggesting the significance of AMPK-independent metabolic pathways. Genetically manipulated animals without molecules of critical significance such as AMPK will tend to acquire compensatory mechanisms. Thus, another approach will be of great help to further understand the role of such key molecules. Thanks to the recent development of analytic systems, it is getting easier to obtain comprehensive information on metabolites. This metabolomics technology has been applied in studies on physical fitness and exercise little by little, providing us with novel findings; although it is not yet popular. Recent results of metabolomic studies in the field of physical exercise, including our investigation demonstrating metabolomic significance of AMPK in contracting skeletal muscle, will be introduced in this review.